2014
DOI: 10.2217/nnm.14.135
|View full text |Cite
|
Sign up to set email alerts
|

Development of Functionalized Nanoparticles for Vaccine Delivery to Dendritic Cells: A Mechanistic Approach

Abstract: The developed nanoparticles might drive antigens to be presented through MHC class I and II molecules to both CD8(+) and CD4(+) T cells, favoring a complete and coordinated immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…Moreover, no significant differences were observed even after 48 h of incubation with 1000 μg/mL of nanoparticles. A similar profile was achieved by Silva et al (2014) with cell viabilities were higher than 70 % after 48 h of incubation of PLGA nanoparticles with JAWSII cells. 29 These results show that the manufacturing process led to nanoparticles which residual amounts of organic solvent and surfactant do not affect the viability of targeted cells.…”
Section: Dendritic Cell Viability In the Presence Of Nanoparticlessupporting
confidence: 73%
“…Moreover, no significant differences were observed even after 48 h of incubation with 1000 μg/mL of nanoparticles. A similar profile was achieved by Silva et al (2014) with cell viabilities were higher than 70 % after 48 h of incubation of PLGA nanoparticles with JAWSII cells. 29 These results show that the manufacturing process led to nanoparticles which residual amounts of organic solvent and surfactant do not affect the viability of targeted cells.…”
Section: Dendritic Cell Viability In the Presence Of Nanoparticlessupporting
confidence: 73%
“…These different metabolic pathways must influence antigen presentation and need to be considered in the development of a vaccine formulation [30]. For example, Silva et al (2014) showed that macropinocytosis, clathrin-mediated endocytosis, and caveolin-and lipid raftdependent endocytosis are involved in the internalization of mannose-grafted PLGA nanoparticles by murine bone marrow-derived DCs. Their formulation allowed the antigen to be presented through both the MHC class I and II pathways, thus inducing a complete immune response [31].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of nanoparticlesand MPLA-mediated toxicity in cells at the concentrations used (250 μg/mL for NPs and between 6.12 μg/mL and 50 μg/mL for MPLA) was in accordance with the literature. Indeed, studies performed with A549 human lung epithelial cells showed that concentrations of PLA-NPs ranging from 2 to 200 μg/mL or concentrations of PLGA-NPs ranging from 0.01 to 4 mg/mL had no effect on cell viability according to analyses performed with MTT and LDH assays [31,32]. Concerning MPLA, Ismaili et al found no cytotoxic effects on human monocyte-derived DCs even at 100 μg/mL [19].…”
Section: Discussionmentioning
confidence: 99%
“…A key advantage of particulate vectors relative to other non-viral gene delivery systems is their superior in vivo stability. The principal types of polymers studied in this context include those made of poly(lactide) (PLA; reviewed in [ 99 ]), poly(lactide-co-glycolide) (PLGA; reviewed in [ 99 , 100 , 102 ]), polyorthoesters [ 103 ], polystyrene (PS) [ 104 , 105 ] and poly(ε-caprolactone) [ 106 ]. Of these, PLGA has been studied most extensively in terms of its capacity to stimulate APCs.…”
Section: Micro-and Nano-particulate Dna Delivery Vectorsmentioning
confidence: 99%